2020
DOI: 10.24093/awej/vol11no3.8
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Graduation Project: Attitudes and Perceived Challenges of Students and Staff at a Libyan EFL Department

Abstract: In 1997, the Department of English (Faculty of Languages, University of Tripoli) canceled Graduation Project (GP) as a graduation requirement primarily due to growing student plagiarism. Two decades on, the Department decided it is time for Returning to Graduation Project (RGP). In preparation for this, a Research Methods (RM) module was delivered to students, and an intense 'research design and methodology' course was taken by the staff. In this exploratory mixedmethods case-study research, the main question … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Instead, many of the students thought that research was interesting and showed very moderate interest in engaging in research as a student researcher. This finding is similar to that found by Elmabruk and Bishti (2020). In addition, most of the students agreed that undergraduate research experience influences their self-perception as graduate students in the future.…”
Section: B Efl Students' Attitudes Towards Conducting Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…Instead, many of the students thought that research was interesting and showed very moderate interest in engaging in research as a student researcher. This finding is similar to that found by Elmabruk and Bishti (2020). In addition, most of the students agreed that undergraduate research experience influences their self-perception as graduate students in the future.…”
Section: B Efl Students' Attitudes Towards Conducting Researchsupporting
confidence: 88%
“…Conducting research on current issues in the EFL fields has been introduced and encouraged among undergraduate students. Despite a large volume of studies investigating EFL students' perceptions of doing research in various contexts (e.g., Elmabruk & Bishti, 2020;Qasem & Zayid, 2019;Yeh, 2009), there has been a dearth of research focusing on this topic in the Vietnamese setting until recently. Even though there have been significant contributions of findings from previous studies in this research strand, it has been long overdue for an in-depth study of the EFL students' perspectives on the necessity of undergraduate research together with their practices.…”
Section: Introductionmentioning
confidence: 99%
“…Research supervision of students' research projects in the final year has been a responsibility of every lecturer at the University of Namibia. For this to work, students are assigned to supervisors who are entrusted with the responsibilities of supervising students throughout the process of the project, and undergraduate students are obliged to undertake a research project to demonstrate writing skills and independence as researchers (Elmabruk & Bishti, 2020). Despite all these, it appears to be a rapid increase in the number of undergraduate students researching at the University of Namibia (UNAM).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is a plethora of literature about undergraduate research supervision internationally (Olsson & Hallberg, 2018;Winchester-See, Rowe & Mackaway, 2016;Reguant, Martínez-Olmo, & Contreras-Higuera, 2018); Lee, 2007;Roberts & Seaman, 2018;Muthanna & Alduais, 2021;Vereijken, van der Rijst, van Driel & Dekker, 2018) and nationally (Elmabruk & Bishti, 2020;Makoni, 2021;Mushoriwa & Nyakutse, 2014;) there seems to be a dearth of literature in the local context which is Namibia, specifically at the University of Namibia's Rundu Campus. Little is known about what may seem to be an ambivalence among lecturers about how to support the writing aspects during a program of a research project in their role as supervisor.…”
Section: Introductionmentioning
confidence: 99%